Papillary fibroelastoma of unusual localization, a case from practice - Vitovskiy, R.; Zakharova, V.; Dyadyun, D.; Isaenko, V.; Semeniv, P. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Papillary fibroelastoma (fibroelastic papilloma, papilloma of valves, valve fibroma) is a benign intracavitary formation originating from the endocardium. PF can affect any department of the heart, but most often - the chordal apparatus and valve flaps. In 10% of cases, the multiple nature of the lesion is noted. In most cases, the left heart is affected. Macrophysically, the PF is usually a small tumor with a diameter of 1.5-2.0 cm, whitish in color, of a soft or dense elastic consistency, reminiscent of papillary growth of the endocardium of Lambl’s. Diagnostics of the PF is extremely difficult, because it hasn’t pathognomonic clinical and laboratory features. The use of echocardiography provided accurate and timely diagnosis of the tumor. The purpose of this work was to demonstrate the features of localization, clinical course and surgical treatment of papillary fibroelastoma of the left ventricle. Materials and methods. As of 01/01/2018,in the NICVS N.M. Amosova , 916 patients with heart tumors were treated. Papillary fibroelastoma was diagnosed in 9 cases, which was 1.0% among all primary heart tumors. Results and discussion. We present the results of the clinical observation of another patient who had a papillary fibroelastoma, localized on the papillary muscle of the mitral valve. According to transthoracic Echo KG, a mobile formation with fuzzy fragmented contours, without a capsule, originating from papillary muscles, 1.6 x 0.8 cm in size, was found in the cavity of the left ventricle. A significant fragmentation of the formation and high mobility of the visualized fragments suggested a high threat of their detachment from subsequent embolic complications. Due to high mobility and fragmentation of formation, it was decided to perform an operation aimed at removing the tumor, in an emergency. Conclusions. The described case demonstrates the possibility of non-valvular localization and asymptomatic flow of papillary fibroelastoma. In this case, the tactics of emergency and radical surgical treatment should always be observed.